Analisis UU Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat (Perspektif Sosial dan Politik Hukum) - Aisyah; Fakina Herliani; Sopian (Institut Agama Islam Negeri Kerinci, 2020)
Zakat is a religious institution that aims to improve justice and welfare of the community so it needs to be regulated to increase the effectiveness and efficienty, zakat must be managed in an institutionalized manner in accordance with Islamic law. Management of zakat is the activity of planning, implementing, and coordinating the collection, distribution and utilization of zakat. Zakat itself means property that must be issued by a Muslim or business entity to be given to those entitled to receive it in accordance with Islamic law. UU No. 23 / 2011 is a regulation governing Zakat Management which cannot be separated from the social and political influence of the law.